Pengaruh Jam Kerja Pemakaian Minyak Lumas terhadap Suhu Mesin Diesel Generator di Kapal - Muchammad Afilla Nurrahman; Nasri Nasri; Wulan Marlia Sandi; Shofa Dai Robbi; Intan Sianturi (Pusat riset dan Inovasi Nasional, 2026)
Generators are one of the important auxiliary aircraft needed on ships for power generation. During the operation of a diesel generator, continuous rotation occurs resulting in friction and erosion of the moving parts. The supporting factor for the smooth running of a diesel engine is a lubrication system that is supported by good lubricating oil quality, besides that it also needs to be supported by an adequate and good cooling system. The use of lubricants is one of the most important factors to ensure the performance of diesel engines. The lubricant is in charge of maintaining the condition of the engine so that it remains stable. This study aims to analyze the effect of using lubricating oil beyond the operating hours limit on engine heat. Furthermore, it also discusses steps to ensure diesel engine temperatures remain normal. This research was carried out during the practice of sailing on a ship for approximately one year. This study uses a descriptive quantitative research method. The primary data obtained directly utilizes observation methods, and documentation. Secondary data was obtained from existing articles and journals. The data analysis techniques used are descriptive analysis and inferential analysis. The results of this study show that the working hours of lubricating oil use have a significant influence on the increase in the temperature of diesel generator engines as evidenced by hypothesis tests on two engine units, namely AE1 and AE2. In the AE1 unit, a t-value of 18.467 with a significance of 0.000 was obtained, while in AE2 the t-value was 14.289 with a significance of 0.000. The significance value in both units is less than 0.05 so it can be concluded that the working hours of lubricated oil have a significant influence on the temperature of the genarato diesel engine on the ship.